Keistimewaan Yogyakarta dan Politik Wacana: Analisis Wacana Visual Media di Ruang Publik - Kamil Alfi Arifin (Jurnal Komunikasi, 2011)
Discourse of Yogyakarta’s privilege status once was dimmed from public memory. But then it return and people start to re-debate in the political uproar that included grass-roots level, after the President snap it. Discursive battle about this issue does not only appear in mainstream mass media stage, but also in outdoor media. This article tries to reveal the discourse of Yogyakarta's privilege status that is represented in outdoor media, as well as to open up the power-relations behind the production of the discourse.